2018
DOI: 10.2147/clep.s177141
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of sporadic <em>Campylobacter</em> infections in Denmark: a nationwide case-control study among children and young adults

Abstract: BackgroundEach year more than 4,000 cases of campylobacteriosis are reported in Denmark, making it the most common bacterial gastrointestinal infection. Here we describe a case-control study to identify sources of infection with a focus on environmental factors.MethodsFrom January to December 2016, we conducted a prospective case-control study among Danish persons aged 1–30 years. Participants were invited by letter to complete an online questionnaire. Crude and adjusted ORs were calculated and final parsimoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…C. jejuni lives as a commensal bacterium in the gastrointestinal tract of wild and domestic birds and mammals, including cattle and sheep. Environmental transmission routes are less frequently reported, but risks include exposure during outdoor sports, swimming in natural waters or contact with garden soil ( Stuart et al., 2010 ; Ellis-Iversen et al., 2012 ; Mughini-Gras et al., 2012 ; Bronowski et al., 2014 ; Mossong et al., 2016 ; Kuhn et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…C. jejuni lives as a commensal bacterium in the gastrointestinal tract of wild and domestic birds and mammals, including cattle and sheep. Environmental transmission routes are less frequently reported, but risks include exposure during outdoor sports, swimming in natural waters or contact with garden soil ( Stuart et al., 2010 ; Ellis-Iversen et al., 2012 ; Mughini-Gras et al., 2012 ; Bronowski et al., 2014 ; Mossong et al., 2016 ; Kuhn et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transmission to humans occurs primarily through unsafe handling or consumption of raw or undercooked chicken, consumption of raw milk, or contact with domestic animals (4-6). However, a large proportion of cases cannot be easily explained by these factors and it has been suggested that other infection routes (e.g., the environment) are equally important in explaining transmission of this disease (4,7). Some zoonotic pathogens such as Shigella spp., Giardia lamblia, and Entamoeba histolytica have been associated with high risk for infection among men who have sex with men (MSM) because of anal-oral contact (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Campylobacteriosis is a zoonotic disease; poultry, wild birds, pets, and farm animals are the main reservoirs. Transmission to humans occurs primarily through unsafe handling or consumption of raw or undercooked chicken, consumption of raw milk, or contact with domestic animals ( 4 6 ). However, a large proportion of cases cannot be easily explained by these factors and it has been suggested that other infection routes (e.g., the environment) are equally important in explaining transmission of this disease ( 4 , 7 ).…”
mentioning
confidence: 99%
“…Climate data (in particular historic temperature and rainfall series), geographical data including geo-coded address data, national data on buildings, data from the population register (to form cohort and control reference populations), and data from the National Patient Register (Tables 4, 5) were extracted and linked. Population-based case-control studies have established consumption of fresh chicken meat (26) and a number of other factors including pets and leisure activities (27) as major risk factors for human infections. Locating human cases addresses, geocoding them and performing register-linkage to housing information showed risk of infection to be pronounced in rural areas in particular among children (28).…”
Section: Details To Understand Key Programmatic Elementsmentioning
confidence: 99%